Effect of ambient temperature on the performance of combined cycle power plant with cooling system in a subtropical region - Hayder Baqer, Mahdi (2016)
The climate conditions have a powerful influence on combined cycle power plant performance as its known. Total output power and overall thermal efficiency of the power plant dropping under the high ambient temperatures that often occur during the hot days. This is a major drawback for combined cycle power plant operated in a subtropical region. In the Middle East where this study was carried out, the ambient temperature typically varies between (15C) and (45C). The Plant has been studied consist of three gas turbines with total power (535MW) and three triple-pressure heat recovery steam generators, addition one steam turbine with (345 MW) output power. The overall thermal efficiency of power plant is (57.7%). In this study, combined cycle power plant was used for assessment of the performance with the changes in ambient air temperature. Two approaches were used to study this phenomenon. Firstly, the performance parameters were calculated by using actual data acquired by the operation history of the power plant. Secondly, the performance was analyzed using thermodynamic principles. Then results of the two approaches were compared and optimizing using RBFNN method. Cooling the gas turbine inlet air can improve the power plant performance substantially. This occurs due to the cooled air is denser, giving the compressor a higher mass flow rate and resulting in increased output power and efficiency of the power plant. Single effect LiBr absorption chiller proposed as a cooling system to cool the ambient air temperature at (15 C). The average reduction in power output per degree Celsius is about (1.82 MW). Cooling of inlet air from (45°C) down to (15°C) would increase the power output around (50.04MW). Where every decline in temperature by (10°C) adding to the total output power of (16 MW). The average reduction in the overall thermal efficiency per degree Celsius is about (0.217%). In addition, the cooling of inlet air from (45°C) down to (15°C) would increase the overall thermal efficiency around (6.091%). Where every decline in the temperature by (10°C), that increases the overall thermal efficiency around (2.03%). The results of using this cooling technique are increasing the total output power and overall thermal efficiency to (875 MW), (58%) respectively. The effect of using radial basis function neural network (RBFNN) technique give the average deviation about (1.2%) and (1.7%) for the power output and thermal efficiency respectively.